Signs of resistance to Melampsora larici-tremulae on species of Pinus hosts of Melampsora pinitorqua: implications regarding the taxonomic relationship between the two rust fungi - A. Paolillo; B. Naldini; F. Drovandi; N. Longo; T. Gonnelli (Phytopathologia Mediterranea, 2002)
Signs of resistance such as cortical necroses which occurred after artificial inoculations with Melampsora larici-tremulae on some species of the genus Pinus in the host range of M. pinitorqua were evaluated. Similar observations were carried out on P. sylvestris inoculated with two provenances of M. larici-tremulae from areas with different environmental conditions. In both experiments, the degree of resistance to M. larici-tremulae depended on how suitable environmental conditions were for both the host and the fungus. The greatest resistance to M. laricitremulae was shown by P. sylvestris.These observations could indicate that P. sylvestris is becoming a nonhost of M. larici-tremulae. The type of host-parasite interaction between some species of Pinus and M. larici-tremulae, when compared to analogous interactions between the same species of Pinus and M. pinitorqua, can shed light on the taxonomic relationship between the two rust fungi.